Enhanced free space beam capture by improved optical tapers - Bartley, Tim; Heim, Bettina; Elser, Dominique Alexander; Sych, Denis; Sabuncu, Metin; Wittmann, Christoffer; Lindlein, Norbert; Marquardt, Christoph; Leuchs, Gerd (2010)
In our continuous variable quantum key distribution (QKD) scheme, the homodyne detection set-up requires balancing the intensity of an incident beam between two photodiodes. Realistic lens systems are insufficient to provide a spatially stable focus in the presence of large spatial beam-jitter caused by atmospheric transmission. We therefore present an improved geometry for optical tapers which offer up to four times the angular tolerance of a lens. The effective area of a photodiode can thus be increased, without decreasing its bandwidth. This makes them suitable for use in our free space QKD experiment and in free space optical communication in general. © Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering 201
Keywords: Atmospheric optics; Beam-jitter; Free space communication; Optical taper; Quantum key distribution; Random media